Pushover Analysis of Steel Seismic Resistant Frames with Reduced Web Section and Reduced Beam Section Connections - Naughton, Daniel Tomas; Tsavdaridis, Konstantinos Daniel; Maraveas, Chrysanthos; Nicolaou, Andreas (Frontiers in Built Environment, 2017)
The widespread brittle failure of welded beam-to-column connections caused by the 1994 Northridge and 1995 Kobe earthquakes highlighted the need for retrofitting measures effective in reducing the strength demand imposed on connections under cyclic loading. Researchers presented the reduced beam section (RBS) as a viable option to create a weak zone away from the connection, aiding the prevention of brittle failure at the connection weld. More recently, an alternative connection known as a reduced web section (RWS) has been developed as a potential replacement, and initial studies show ideal performance in terms of rotational capacity and ductility. This study performs a series of non-linear static pushover analyses using a modal load case on three steel moment-resisting frames of 4-, 8-, and 16-storeys. The frames are studied with three different connection arrangements; fully fixed moment connections, RBSs and RWSs, in order to compare the differences in capacity curves, inter-storey drifts, and plastic hinge formation. The seismic-resistant connections have been modeled as non-linear hinges in ETABS, and their behavior has been defined by moment-rotation curves presented in previous recent research studies. The frames are displacement controlled to the maximum displacement anticipated in an earthquake with ground motions having a 2% probability of being exceeded in 50 years. The study concludes that RWSs perform satisfactorily when compared with frames with fully fixed moment connections in terms of providing consistent inter-storey drifts without drastic changes in drift between adjacent storeys in low- to mid-rise frames, without significantly compromising the overall strength capacity of the frames. The use of RWSs in taller frames causes an increase in inter-storey drifts in the lower storeys, as well as causing a large reduction in strength capacity (33%). Frames with RWSs behave comparably to frames with RBSs and are deemed a suitable replacement.